Islamization of Local Traditions in Barus, Central Tapanuli - Sitanggang, Wahida; Maraimbang, Maraimbang (FiTUA: Jurnal Studi Islam, 2025)
The Islamization of local traditions in Barus, Central Tapanuli, is a significant event in the history of Islam's spread in the Indonesian archipelago. As a trading hub since the 7th century AD, Barus became a gateway for Muslim merchants and scholars from the Middle East, Persia, and Gujarat. This study aims to explain the process of Islamization through cultural adaptation and peaceful da'wah, emphasizing the purification of faith while preserving local traditions that align with the principles of tawhid (monotheism). The research employs a qualitative method with a historical and descriptive-analytical approach, examining historical sources, ancient manuscripts, and interviews with historians and religious leaders. The findings reveal that Islamization in Barus occurred peacefully and persuasively, transforming local traditions such as customary rituals, leadership systems, and social norms into Islamic values. This process not only strengthened the community's belief in tawhid but also led to the establishment of Islamic institutions and the emergence of scholars who played crucial roles in the development of Islam in the region.